Definição e avaliação de um modelo genérico para coleta de dados e geração de representações visuais de interações de aprendizagem em jogos educacionais - Cardoso, Frederico Corrêa (Universidade Federal de São Carlos, 2019)
The use of educational games by teachers in their classes can have a significant and positive impact on their students’ learning and development skills. There are, however, some difficulties that can jeopardize the follow-up and assessment of the students while they are playing. This work presents a generic solution that can be applied to many kinds of educational games and offer a support for teachers to analyze, monitor and assess their students. Based on Information Visualization concepts, Learning Analytics and Game Learning Analytics, many steps were taken towards our goal. The first step comprised a survey of the main indicators that teachers find relevant. We invited 37 of them to answer an online questionnaire in order to understand their main difficulties and find out which analysis tools they needed. Doing so we were able to define a set of engagement indicators that were considered to be relevant by the teachers. The second step comprised the definition of which data should be collected from the games for each indicator. In the third step we developed a dashboard with a set of visual representations of each one of the indicators. To accomplish this, we used three educational games available at the REMAR Platform, each with different charecteristics. Finally, we then invited four teachers to assess our dashboard through an online questionnaire to check for clarity and understandability of the graphics we presented, as well as the dashboard usability. The teachers’ response gave us a strong sense that our goal was reached and that we developed a tool that is useful for the monitoring and evaluation of the students.
Definition and evaluation of a generic model for data collection and generation of visual representations of learning interactions in educational games
Keywords: Analítica de Aprendizagem em Jogos; Analítica de aprendizagem; Jogos educacionais; Visualização da informação; Dashaboard; Game learning analytics; Learning analytics; Educational games; Information visualization; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO